Synthesis, Characterization and Antibacterial Studies of Some Transition Metal Complexes of a Schiff Base Derived from 2-(Aminomethyl)- benzimidazole and Thiophene-2-carbaxaldehyde - Pragathi Jogi; K. Mounika; M. Padmaja; Lakshmi M.; C. Gyanakumari (E-Journal of Chemistry)
Complexes of Cu(II), VO(IV), Mn(II), Co(II), Ni(II) and Zn(II) with a Schiff base derived from 2-(aminomethyl)benzimidazole and thiophene-2-carbaxaldehyde (1-(1H-benzimidazol-2-yl)-N-[(E) thiophenylmethylidene] methanamine-BNTM) were successfully synthesized. The complexes have been characterized using chemical analysis, spectroscopic methods (IR, UV-Visible, 1H- NMR, 13C-NMR and ESR), Thermal studies, conductometric and magnetic data. According to these data, we proposed an octahedral geometry to all the metal complexes. Antibacterial activity of the ligand and its metal complexes were studied against two gram-negative bacteria; Escherichia coli, Pseudomonas aeruginosa and two gram-positive bacteria; Bacillus subtilis, Staphylococcus aureus. It has been found that all the complexes are antimicrobially active and show higher activity than ligand.